Analysis of Independent Practice Midwifes in West Pasaman District Using Partograph in Normal Delivery Care - Larasati, Timmy; Dewi, Ratna (PT. Riset Press International, 2024)
The maternal mortality rate (MMR) and infant mortality rate (IMR) are key performance indicators for a nation. For every Indonesian population, MMR and IMR represent one of the parameters of optimal health status. In an effort to lower the MMR, health professionals are urged to use Partograph to track the progress of labor and make appropriate decisions if pathological conditions are discovered. It has been demonstrated that the Partograph works well for both identifying irregularities in labor and preventing prolonged labor. The purpose of the study is to find out how Partograph are used by midwives at the Independent Midwife Practice in the West Pasaman district. Since the informants for this research are independent practice midwives, the qualitative descriptive research method will be used to collect data through focus group discussions (FGD), in-depth interviews, and observations. Data analysis: By deciphering, writing up, and drawing conclusions from in-depth interviews conducted with key informants and two discussion groups. The research's conclusions are based on the findings of two focus groups and two key informant interviews. Specifically, Partograph are used by independent practice midwives to aid in childbirth; some midwives have also used them to track the progression of labor, particularly for patients with birth insurance so they can claim delivery expenses. The Partograph is filled all the way, but occasionally it is filled after delivery. The only reason partography is applied is to obtain Jampersal fees; independent practical midwives are knowledgeable about partography and have a positive attitude toward it. Organizational policies and leadership for IBI are still lacking.